Effects of epilepsy control following decompressive craniectomy on mortality and morbidity in epileptic patients with malignant MCA infarction (Annals of Medical Research, 2021)
Aim: The present study aims to investigate the effects of seizure or epilepsy formation on mortality and morbidity in epileptic patients after craniectomy.Material and Methods: The patients were divided into the following groups: Group 1, those who had no seizures, but were routinely treated with 3x100 mg of epanutin daily (n=6), Group 2, those who had at least one or multiple seizures and were initiated a second antiepileptic drug in addition to 3x100 mg of epanutin daily (n=13), and Group 3, those who had multiple seizures and who were sedated or narcotized in addition to being treated with 3x100 mg of epanutin daily (n=7). All patients underwent decompressive craniectomy within a maximum period of 48 hours and their characteristics such as age, gender, localization of infarct, hemiplegia, monoplegia, operation time, Glasgow coma and outcome scales were recorded. Results: According to the Glasgow Outcome Scale, 1 patient in Group 1, 8 patients in Group 2 and 6 patients in Group 3 died and there was a significant increase in patient losses in Group 2 and Group 3 compared to Group 1 (p0.05). 10 patients continued to live their lives with the support of home-care services and 2 patients with other forms of help. Conclusion: It was seen that there is a high incidence of seizure and epilepsy in MMCA infarcts after decompressive craniectomy and this significantly increased mortality or dysfunctional recovery if epilepsy could not be brought under control.